Effect of cardiac rehabilitation therapy on depressed patients with cardiac insufficiency after cardiac surgery - Zhang Wenyu; Zhu Guangjian; Li Beibei; Chen Chen; Zhu Yingzhi (Open Medicine, 2023)
This study aims to analyze the effect of cardiac rehabilitation therapy on cardiac autonomic nervous function in patients with cardiac insufficiency complicated with anxiety depression after cardiac operation to provide a reference for clinical practice. A total of 109 patients subject to cardiac operation in our hospital from January 2020 to March 2023 were enrolled as study subjects, including 50 patients who received conventional rehabilitation therapy (control group) and 69 patients who received cardiac rehabilitation therapy (research group). Before and after treatment, the left ventricular ejection fraction (LVEF) and central venous pressure (CVP) were determined, and the level of N-terminal pro-B-type natriuretic peptide (NT-proBNP) was measured. Low frequency/high frequency (LF/HF), standard deviation of normal to normal (SDNN), and root mean of successive square differences (RMSSD) were measured by a multi-lead ECG system. Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), Pittsburgh Sleep Quality Index (PSQI), Activity of daily living (ADL), and Barthel Index (BI) were applied for corresponding investigations, as well as the 6-min walk test (6MWT). After treatment, the research group showed higher LVEF, CVP, LF/HF, SDNN, and RMSSD, and lower NT-proBNP, SAS, and SDS than the control group (P < 0.05). Significantly elevated ADL score, BI, and 6MWT and reduced PSQI were observed in both groups after treatment, with more remarkable changes in the research group (P < 0.05). In conclusion, cardiac rehabilitation therapy effectively improved the cardiac function of patients with cardiac insufficiency complicated with anxiety and depression after the cardiac operation and alleviated their negative emotions.